Physiologic effects of different hemodynamic patterns of LVAD - Jiahao Mao; Zhen Gao; Wenyuan Yu; Yang Yu (Frontiers in Cardiovascular Medicine)
Left ventricular assist device (LVAD) is an important treatment for patients with end-stage heart failure, which essentially replaces the left ventricle's pumping action to improve peripheral circulation. Its hemodynamic pattern (pulsatile vs. continuous flow) has been a popular research topic in the field. Because of its dependability and endurance, the continuous flow LVAD (CFVAD), as opposed to the first generation of pulsatile flow LVAD (PFVAD), has gained popularity as a mechanical support device in clinical practice in recent years. Many of the complications that arise with CFVAD application are thought to be related to reduced pulsatility. This article provides a review of the physiologic effects of different hemodynamic patterns on the circulatory system and the difference in outcomes of PFVAD vs. CFVAD.